The development of a hairless phenotype in barley roots treated with gold nanoparticles is accompanied by changes in the symplasmic communication - Milewska-Hendel, Anna; Witek, Weronika; Rypień, Aleksandra; Zubko, Maciej; Baranski, Rafal; Stróż, Danuta; Kurczyńska, Ewa U (Scientific reports, 2019)
Uptake of water and nutrients by roots affects the ontogenesis of the whole plant. Nanoparticles, e.g. gold nanoparticles, have a broad range of applications in many fields which leads to the transfer of these materials into the environment. Thus, the understanding of their impact on the growth and development of the root system is an emerging issue. During our studies on the effect of positively charged gold nanoparticles on the barley roots, a hairless phenotype was found. We investigated whether this phenotype correlates with changes in symplasmic communication, which is an important factor that regulates, among others, differentiation of the rhizodermis into hair and non-hair cells. The results showed no restriction in symplasmic communication in the treated roots, in contrast to the control roots, in which the trichoblasts and atrichoblasts were symplasmically isolated during their differentiation. Moreover, differences concerning the root morphology, histology, ultrastructure and the cell wall composition were detected between the control and the treated roots. These findings suggest that the harmful effect of nanoparticles on plant growth may, among others, consist in disrupting the symplasmic communication/isolation, which leads to the development of a hairless root phenotype, thus limiting the functioning of the roots.
Keywords: Gene Expression Regulation, Plant; Water; Cell Membrane; voda; epidermis rostlin; Hordeum; kořeny rostlin; zlato; regulace genové exprese u rostlin; kovové nanočástice; Metal Nanoparticles; Nutrients; buněčná diferenciace; Plant Epidermis; živiny; Gold; Seedlings; ječmen (rod); látky znečišťující půdu; buněčná membrána; Plant Roots; semenáček; Cell Differentiation; Soil Pollutants